Natural Occurring and Engineered Enzymes for Peptide Ligation and Cyclization - Nuijens, Timo; Toplak, Ana; Schmidt, Marcel; Ricci, Antonio; Cabri, Walter (Frontiers in Chemistry, 2019)
The renaissance of peptides as prospective therapeutics has fostered the development of novel strategies for their synthesis and modification. In this context, besides the development of new chemical peptide ligation approaches, especially the use of enzymes as a versatile tool has gained increased attention. Nowadays, due to their inherent properties such as excellent regio- and chemoselectivity, enzymes represent invaluable instruments in both academic and industrial laboratories. This mini-review focuses on natural- and engineered peptide ligases that can form a new peptide (amide) bond between the C-terminal carboxy and N-terminal amino group of a peptide and/or protein. The pro’s and cons of several enzyme classes such as Sortases, Asparaginyl Endoproteases, Trypsin related enzymes and as a central focus Subtilisin-derived variants are summarized. Most recent developments with regards to ligation and cyclisation are highlighted.